AI-Powered Adaptive Learning Media for ECDIS Training in Indonesian Maritime Education Management (Digital Navigation Pedagogy) - Panderaja Soritua Sijabat; Marudut Bernadtua Simanjuntak (IJECA (International Journal of Education and Curriculum Application), 2026)
The rapid digitalization of maritime bridge operations demands comprehensive transformation in nautical deck officer education and maritime training management systems. This qualitative design-based research investigates the development, implementation, and management effectiveness of AI-powered adaptive learning media integrating ECDIS simulators, virtual reality navigation scenarios, and intelligent tutoring systems across seven Indonesian maritime academies under Ministry of Transportation governance. Guided by four objectives spanning platform design, organizational management analysis, competency evaluation, and framework development the study employed purposeful multi-stakeholder sampling involving 520 nautical students, 95 maritime technology instructors, 68 shipping company officers, and 42 educational specialists across three iterative development cycles. Data were generated through in-depth semi-structured interviews, focus group discussions, classroom observations, document analysis, and thematic analysis, with trustworthiness ensured through member checking and multi-source triangulation. Findings reveal substantial navigational competency enhancements in ECDIS operational proficiency, spatial awareness, and technology integration skills, while simultaneously demonstrating that these gains are contingent upon systemic organizational management conditions including strategic leadership commitment, dedicated resource allocation, sustained instructor professional development, and robust sustainability mechanisms. Addressing a gap in existing literature on technology implementation within non-university, sector-ministry-governed maritime education, this study contributes the Maritime Technology-Enhanced Learning (M-TEL) Framework: an evidence-based implementation model offering actionable guidelines for maritime institutions and Ministry of Transportation policy officials pursuing pedagogically effective, organizationally feasible, and institutionally sustainable technology-enhanced education.